Associations between Unplanned Pregnancy, Low Social Support, Domestic Violence, and Intrapartum Complication, with Postpartum Depression: Meta Analysis (Journal of Maternal and Child Health, 2024)
Background: The postpartum period is a period where the risk of depression and other mental disorders generally increases due to the physiological and psychosocial changes that occur. The aim of this study was to measure the relationship using the meta-analysis method of unplanned pregnancy, poor social support, domestic violence, complications during childbirth with the incidence of postpartum depression..Subjects and Method: This research is a systematic review and meta-analysis. Article searches were carried out using PICO. Population: Postpartum women. Interventions: unplanned pregnancy, poor social support, domestic violence, and complications during childbirth. Comparison: planned pregnancy, good social support, no domestic violence, and no complications during childbirth. Outcome: Postpartum depression. The keywords used in the article search were "postpartum depression" AND "unplanned pregnancy" AND "poor social support" AND "intimate partner violence" AND “delivery complications”. Articles were obtained from several databases including Google Scholar, Pubmed, Science Direct from 2015-2023. Data is processed using the Review Manager Application (RevMan 5.3)Results:  Meta-analysis of 11 cross-sectional studies showed that unplanned pregnancy increased the risk of postpartum depression (aOR= 2.69; 95% CI= 2.30 to 3.16; p= 0.001). Meta-analysis of 11 cross-sectional studies showed that low social support increased the risk of postpartum depression (aOR= 2.35; 95% CI= 1.46 - 3.79; p= 0.004). Meta-analysis of 7 cross-sectional studies showed that partner violence increased the risk of postpartum depression (aOR= 2.82; 95% CI= 1.81 - 4.40; p= 0.001). Meta-analysis of 6 cross-sectional studies showed that complications during delivery increased the risk of postpartum depression (aOR= 2.20; 95% CI= 1.75 to 2.77; p= 0.001).Conclusion: Unplanned pregnancies, poor social support, partner violence, and complications during childbirth increase the risk of postnatal depression.
Keywords: unplanned pregnancy; social support; partner violence; postpartum depression